The extraordinary life of an ordinary man : a memoir - Newman, Paul, 1925-2008 (Alfred A. Knopf, 2022)
"The raw, candid, unvarnished memoir of an American icon Several years before he died in 2008, Paul Newman commissioned his best friend to interview actors and directors he worked with, his friends, his children, his first wife, his psychiatrist, and Joanne Woodward, to create an oral history of his life. After hearing and reading what others said about him, Newman then dictated his own version of his life. Now, this long-lost memoir-90% Newman's own narrative, interspersed with wonderful stories and recollections by his family, friends, and such luminaries as Elia Kazan, Tom Cruise, George Roy Hill, Martin Ritt-will be published. This book will surprise and even shock people, it reveals unknown sides of Paul Newman: funny and tragic, charming and insightful, personal and professional. Newman's traumatic childhood is brilliantly detailed: his terrible relationship with his mother (he says she always considered him purely a decoration, not an actual child), his complicated relationship with his father (who once insisted eight-year-old Paul walk home several miles with a broken leg). He talks with extraordinary honesty, insight and humor, about his insecurities as a teenager, his lack of success with women, his feelings of failure. Tales of his army years feel like a movie in itself. His college years, his early yearnings to be an actor, learning his craft, his acting rivals at the beginning of his career (Brando and Dean), his films (good and bad) - he spares no one, including himself. He discusses the complicated relationship he had with his first wife, his son Scott's death, and his guilt about that death. Perhaps the most moving material in the book comes when he discusses Joanne Woodward-their love for each other, his dependence on her, even their sexually charged life together"--